Endometrial Cryoablation for the Treatment of Heavy Menstrual Bleeding: 36-Month Outcomes from the CLARITY Study - Curlin HL; Anderson TL (Dove Medical Press, 2022)
Howard L Curlin, Ted L Anderson Department of Obstetrics and Gynecology, Vanderbilt University Medical Center, Nashville, TN, USACorrespondence: Howard L Curlin, Email howard.curlin@vumc.orgStudy Objective: To examine long-term outcomes from the pivotal study that evaluated the safety and effectiveness of the Cerene® Cryotherapy Device (Channel Medsystems, Berkeley, CA) in premenopausal women with heavy menstrual bleeding due to benign causes who have completed childbearing.Methods: The prospective, multicenter, single-arm, open-label study had eight sites in the USA, one in Mexico, and two in Canada. Inclusion criteria included uterine sound ≤ 10 cm, endometrial cavity length 2.5 to 6.5 cm, age 25 to 50 years, a pictorial blood loss assessment chart score of ≥ 150, no submucosal myomata and/or uterine obstruction, distortion, or abnormality. A total of 242 subjects underwent a 2.5-minute cryoablation. Long-term follow-up visits were conducted at Month 24 and Month 36. Data collected included gynecological adverse events, description of last menstrual period, contraception status, self-report of pregnancy, medical or surgical interventions to treat abnormal uterine bleeding, satisfaction, recommendation, and quality of life (QoL). QoL outcomes were measured with the Menorrhagia Impact Questionnaire (MIQ) and the Premenstrual Symptoms Impact Survey (PMSIS™).Results: 201 subjects completed their Month 36 final study visit. Subject outcomes were comparable to those at Month 12. Eighty-nine percent of subjects reported amenorrhea, a lighter-than-normal, or normal period, 91% of subjects had no or slight limitations in MIQ measured activities, and 85% reported premenstrual symptoms at a low frequency. Eighty-five percent of the subjects were satisfied or very satisfied. The cumulative incidence of hysterectomy was 5% and reintervention was 8.7%. Forty-nine gynecologic adverse events (AE) were reported; one non-serious AE, postcoital bleeding, was reported as related to the procedure. No serious device-related or procedure-related AEs were reported.Conclusion: Study data demonstrate that the positive effects of Cerene Cryotherapy Device treatment are sustained through Month 36 and that the risks associated with the device and procedure are low (ClinicalTrials.gov; NCT02842736).Keywords: ablation, endometrial, menorrhagia, cryotherapy